2018
DOI: 10.1186/s13195-018-0443-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into globalization: comparison of patient characteristics and disease progression among geographic regions in a multinational Alzheimer’s disease clinical program

Abstract: BackgroundGlobalization of clinical trials has important consequences for trial planning and interpretation. This study investigated heterogeneity in patient characteristics and outcomes among world regions in the global idalopirdine Phase 3 clinical program.MethodsData were pooled from three 24-week randomized controlled trials in patients aged ≥ 50 years with mild-to-moderate Alzheimer’s disease (AD) (n = 2506). Patients received idalopirdine (10, 30, or 60 mg/day) or placebo, added to cholinesterase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Alternatively, a recent review of an antidepressant clinical trial found no significant difference in dropout between academic and non-academic sites [ 15 ]. Multinational trials are essential to regulatory goals and a thorough understanding of drug safety, but may carry increased risk of variability, including differences in the proportions of enrolled study partner dyad types by geographic region [ 16 , 17 ]. Completion rates also may differ among global geographic regions in multinational trials [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a recent review of an antidepressant clinical trial found no significant difference in dropout between academic and non-academic sites [ 15 ]. Multinational trials are essential to regulatory goals and a thorough understanding of drug safety, but may carry increased risk of variability, including differences in the proportions of enrolled study partner dyad types by geographic region [ 16 , 17 ]. Completion rates also may differ among global geographic regions in multinational trials [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such biomarker-based synchronization of patient's disease stage would enable testing a drug in a more homogeneous population. This would in turn greatly increase the power of clinical trials in AD where it is common to see extreme levels of variability in patient trajectories (Cummings et al, 2018 ; Ballard et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the developed countries like the US and Canada have a stable economy and have established funding agencies and research organizations that provide funding for research and conducts epidemiological, clinical, and pre-clinical studies on mental health diseases like AD. It is estimated that AD is one of the most financially costly diseases and managed by federal government funding agencies in developed nations [9]. The total estimated worldwide cost of dementia was US$ 818 billion in 2015, which represents 1.09% of global GDP and by 2018, the global cost of dementia raises above US$ 1 trillion.…”
Section: Introductionmentioning
confidence: 99%